PELATIHAN SENI HADRAH DI SMP SULTAN AGUNG SEYEGAN SLEMAN YOGYAKARTA - Hidayatullah (LPPM IST AKPRIND Yogyakarta, 2021)
Hadrah is one of the Islamic art of music that has its own characteristics. This music isusually played during celebrations or Islamic holidays such as the Prophet's birthday, Isra'Mi'raj, Islamic New Year and so on. However, it is unfortunate that this tambourine art hasvery few enthusiasts. Ironically, if we ask the younger generation today, most of them saythey don't know, but if they ask about any online games they know and understand. Thissituation is very concerning, one side we are advancing in the world of digital technology,on the other hand we experience a local cultural crisis, especially local Islamic culture. Toanticipate this, we, through LPPM AMA Yogyakarta, are called to provide training in theart of Hadrah to students of SMP Sultan Agung Seyegan Sleman as a form of communityservice. The hadrah training is carried out once a week on Monday afternoons as a form ofextracurricular school activities. The forms of training are (1) training on tambourine hittingmethods, (2) training on combining various tambourine sounds, (3) vocal training forsholawatan. Through this activity, it is hoped that harmony will be built between students sothat they can stay in touch with each other, and create Islamic character education instudents.